The Association of Serum Adipokines, Insulin Resistance and Vitamin D Status in Male Patients with Androgenetic Alopecia - Wu Y; Hui Y; Liu F; Chen H; Liu K; Chen Q; He Y; Hong N; Yan W; Kong Q; Sang H (Dove Medical Press, 2023)
YiFan Wu,1,* Yun Hui,2,* Fang Liu,2 Huan Chen,2 KeHan Liu,1 QiYing Chen,2 YiFan He,1 Nan Hong,2 WenLiang Yan,2 QingTao Kong,2 Hong Sang1,2 1Nanjing Medical University, Nanjing, 210002, People's Republic of China; 2Department of Dermatology, Jinling Hospital, Nanjing University, Nanjing, 210002, People's Republic of China*These authors contributed equally to this workCorrespondence: QingTao Kong; Hong Sang, Jinling Hospital, Nanjing, Jiangsu, People's Republic of China, Tel +86 025-80860092, Email kongqingtao2008@163.com; sanghong@nju.edu.cnBackground: The frequent coexistence of obesity and metabolic syndrome in patients with Androgenetic alopecia (AGA), may indicate a common pathogenetic pathway with adipokines being a possible implicating cytokine.Objective: This study was conducted to investigate the changes in serum levels of adipokines, insulin resistance, vitamin D status and their relationship with AGA, and the relationship between serum levels of adipokines and insulin resistance.Methods: 80 male patients with AGA were selected as the experimental group and 60 healthy males served as the control group. Both the AGA group and healthy control group were divided into 2 groups according to the presence or absence of insulin resistance (IR): the IR group and the NIR group. Serum levels of leptin, adiponectin, resistin, visfatin, insulin and 25(OH)D were evaluated in all subjects.Results: Compared with the control group, AGA patients showed higher serum levels of leptin and lower adiponectin/leptin (Adpn/Lep) ratio (P< 0.05), and both were positively correlated with the severity of the disease. Compared with the AGA NIR group, serum leptin levels were increased in the AGA IR group (P< 0.05). AGA IR group and AGA NIR group possessed lower Adpn/Lep ratio when compared with the healthy IR group and healthy NIR group respectively (P< 0.05). The multi-factor logistic regression analysis results showed decreased Adpn/Lep level and increased leptin level as risk factors for AGA. AGA Patients had lower vitamin D levels than healthy controls (P< 0.05).Conclusion: Patients with AGA show an imbalance between pro- and anti-inflammatory adipokines, and probably be involved in AGA pathogenesis. Insulin resistance may influence levels of adipokines, but the present findings cannot indicate insulin resistance plays a role in the onset of AGA. The insufficiency and deficiency of vitamin D are common health concern in our subjects and may be involved in the dysfunction of adipocytes and the development of AGA.Keywords: androgenetic alopecia, adipokines, leptin, vitamin D